Formation of a healthy corporate culture in a medical organization - Naumenko Галина (Psychosomatic Medicine and General Practice, 2020)
The health care system is a complex socio-economic mechanism, which is designed to ensure the implementation of the most important social principle - maintaining and improving the health of the population, providing highly qualified treatment and prevention care. Important to remember that healthcare organizations have two stakeholders: doctors and patients (internal and external client). Often, attention is paid only to patients, but it is worth starting with the formation of the commitment of health professionals to the work organization, to create a positive image. Unfortunately, the image of the organization is often formed spontaneously. The reason for this is not only the reluctance of managers to deal with this problem but also the lack of experience and knowledge in the field of image formation and corporate culture of the organization. Culture is elusive, but its impact is easily traced in the daily behavior of employees of any level. Defining goals, setting goals, developing patterns of behavior and attitudes at work and the actual activity within the organization are mediated by its ideology. Elements of culture are reflected in the official vision of the medical institution, and thus become accessible to the external environment - patients, partners, competitors and society as a whole. An established healthy corporate culture is an important management tool, creates strong competitive advantages, increases the social responsibility of medical organizations to society and patients, improves the quality of medical activities. The presence of corporate culture, values and behaviors allow improving the processes of strategic development, internal communication, unity and cohesion of the team, to reduce staff turnover in the organization. The system of continuing professional education of doctors and heads of health care institutions should provide for the implementation of educational programs in the field of formation and development of the corporate culture of medical organizations.